DSP를 이용한 자동고장구분개폐기의 제어장치 개발 - 禹天熙(Chun-Hee Woo); 韓泰煥(Tae-Hwan Han) (전기학회 논문지 P권, 53(3), 2004)
In this study, We developed the microprocessor based controller for Auto Section Switch(ASS). This is installed at consumer's medium-high voltage(load capacity is below 4,000 kVA) switchgear. This function is cooperate with protection device of fault section and automatically dividing the section. And It is designed by Air putter type extinction structure and adopt the mechanism and breaking part module of existing Load Breaker Switch. In addition, We successfully conducted the operation test and checked main function of proto-type.